2002
DOI: 10.1176/appi.ajp.159.9.1514
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Genetic Risk and Fetal Hypoxia to Hippocampal Volume in Patients With Schizophrenia or Schizoaffective Disorder, Their Unaffected Siblings, and Healthy Unrelated Volunteers

Abstract: These findings suggest that in patients with schizophrenia spectrum disorders, hippocampal volume is influenced in part by schizophrenia susceptibility genes and an interaction of these genes with fetal hypoxia. They further suggest that hippocampal volume in schizophrenia or schizoaffective disorder may be linked to time of disease onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(133 citation statements)
references
References 36 publications
6
122
2
3
Order By: Relevance
“…Adult diseases such as schizophrenia have also been linked to infection, fetal malnutrition, or hypoxia in early life (Dalman et al, 1999;Van Erp et al, 2002;Boksa and El-Khodor, 2003). A study by Bilbo et al (2005) showed that perinatal exposure to an infectious agent affected how the nervous system responded to an immune challenge and memory consolidation later in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Adult diseases such as schizophrenia have also been linked to infection, fetal malnutrition, or hypoxia in early life (Dalman et al, 1999;Van Erp et al, 2002;Boksa and El-Khodor, 2003). A study by Bilbo et al (2005) showed that perinatal exposure to an infectious agent affected how the nervous system responded to an immune challenge and memory consolidation later in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Familial risk may determine hippocampal volume loss, 19 which may be both heritable and linked to the specific genetic risk for schizophrenia. 7,20 However, Stefanis and colleagues 21 found no evidence of familial effects once patients with a history of obstetric complications were removed from their analysis, 21 whereas Van Erp and colleagues 22 suggested a gene × environment interaction involving perinatal hypoxic insult to the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,[7][8][9][10] A recent review by Schmidt-Kastner and colleagues 11 suggested that susceptibility genes for schizophrenia were more likely than randomly selected genes to be regulated by hypoxia/ischemia and/or expressed in the cerebrovasculature. In fact, a substantial fraction of the genes reported to be significantly associated with schizophrenia in at least two published studies fit this description, even though only 1-2% of known genes are involved in hypoxia-induced regulation.…”
Section: Introductionmentioning
confidence: 99%